KEBIJAKAN DALAM PENCAPAIAN STANDAR PELAYANAN MINIMAL SMP DI DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN KUBU RAYA - Sukaman, Sukaman; Wahyudi, Wahyudi; M.Chiar, M.Chiar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe government determines national policies and national education standards to guarantee the quality of national education. The Government and the Regional Government must provide services and facilities, and guarantee the implementation of quality education for every citizen without discrimination based on the Minimum Service Standards. The purpose of this study is to obtain descriptive information about the Policy in Achieving Minimum Service Standards for Junior High School which is focused on the perceptions of structural officials, policies, policy formulations and constraints in implementing policies to meet minimum service standards in Kubu Raya Regency. This research uses a qualitative approach with case study, primary and secondary data through interviews, observation and documentation. Based on the conclusions and research suggestions concluded that structural officials' perceptions of Minimum Service Standards are still lacking, the implementation is already underway, the formulation of policies is teachers with academic qualifications and the constraints are infrastructure and human resources that are still not supportive and ready. Keywords: Policies and Minimial Service Standards